ChemInform Abstract: Acid‐Base Properties and Catalytic Activity of Metal‐Organic Frameworks: A View from Spectroscopic and Semiempirical Methods. Issue 40 (September 2016) - Panchenko, Valentina N.; Timofeeva, Maria N.; Jhung, Sung Hwa
Abstract: Review: 313 refs.